Palaeoenvironmental dynamics of Holocene shoreface bryoliths from the southern coast of Brazil. (April 2019) - Tâmega, Frederico Tapajós de Souza; Spotorno-Oliveira, Paula; Dentzien-Dias, Paula; Buchmann, Francisco Sekiguchi; Vieira, Leandro Manzoni; Macario, Kita; Nash, Merinda; Guimarães, Renato Bastos; Francischini, Heitor; Bassi, Davide
Beds of free-living coated nodules (coralline algae, bryozoans, acervulinid foraminifera) create shallow-water carbonate biogenic benthic habitats, which are sensitive to human disturbance and slow to recover. Holocene bryoliths, ranging from sub-spheroidal, sub-discoidal to sub-ellipsoidal in shape, were found scattered in the foredunes in ca. 30-km stretch along the Hermenegildo and Concheiros do Albardão beaches on the southernmost coast of Brazil (Santa Vitória do Palmar municipality, Rio Grande do Sul State). The dominating bryozoan species forming the bryolith is Biflustra holocenica Vieira, Spotorno-Oliveira and Tâmega sp. nov. The inner bryolith arrangement, generally asymmetrical, shows multilamellar and circumrotatory growth of colonies that envelop the bivalve Ostrea puelchana . Bryozoans and subordinate corals characterize the outer bryolith surfaces. The ichnogenera Gastrochaenolites (made by the boring bivalve Lithophaga patagonica ) and Caulostrepsis occur throughout the bryoliths, from the inner part up to the outer surface. The studied bryoliths, originated in a shoreface setting at ca. 7910–7620 cal. yr BP and during subsequent storm waves, were resedimented onto the foreshore and foredunes (to ca. 5700 cal. yr BP) where the bryoliths were finally fossilized.